2017
DOI: 10.1155/2017/2397429
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pneumococcal Disease: Still Lots to Learn and a Need for Standardized Data Collection Instruments

Abstract: Background. Large studies of invasive pneumococcal disease (IPD) are frequently lacking detailed clinical information. Methods. A population-based 15-year study of IPD in Northern Alberta. Results. 2435 patients with a mean age of 54.2 years formed the study group. Males outnumbered females and Aboriginal and homeless persons were overrepresented. High rates of smoking, excessive alcohol use, and illicit drug use were seen. Almost all (87%) had a major comorbidity and 15% had functional limitations prior to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 55 publications
0
21
0
1
Order By: Relevance
“…As mentioned above, the first description of cardiac complications in pneumococcal CAP was reported in 2007 [ 10 ], while in 2008, a case study was published of a 65-year-old woman with Takotsubo cardiomyopathy associated with pneumococcal sepsis [ 42 ]. More recently, a 15-year population-based study of patients with IPD (mean age of 54.2 years), many of whom had a significant co-morbidity, documented frequencies of myocardial infarction, pulmonary embolism, and new onset stroke in 1.5%, 1.3% and 1.1% of patients respectively [ 43 ]. Of those that had an echocardiogram during their infection, 35% were noted to have impaired ventricular function.…”
Section: Cardiac Complications Of Capmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the first description of cardiac complications in pneumococcal CAP was reported in 2007 [ 10 ], while in 2008, a case study was published of a 65-year-old woman with Takotsubo cardiomyopathy associated with pneumococcal sepsis [ 42 ]. More recently, a 15-year population-based study of patients with IPD (mean age of 54.2 years), many of whom had a significant co-morbidity, documented frequencies of myocardial infarction, pulmonary embolism, and new onset stroke in 1.5%, 1.3% and 1.1% of patients respectively [ 43 ]. Of those that had an echocardiogram during their infection, 35% were noted to have impaired ventricular function.…”
Section: Cardiac Complications Of Capmentioning
confidence: 99%
“…The risk of heart failure in patients who had previously developed CAP was higher in patients > 65 years compared to younger patients; nonetheless even in the younger cases the risk was raised and was greater than in the control group of patients. These authors highlighted not only the need to screen for, and to institute preventative strategies to modify risk factors for cardiac events in patients who have had CAP, but also to consider vaccination against pathogens such as the pneumococcus and influenza to prevent CAP [ 14 , 43 ].…”
Section: Cardiac Complications Of Capmentioning
confidence: 99%
“…В настоящее время бактерии Streptococcus pneumoniae (pneumococcus) являются основной этиологической причиной развития внебольничной пневмонии и отитов как у детей [1,20], так и у взрослых людей [14]. Только в Соединенных Штатах Америки ежегодно регистрируется более 500 000 случаев пневмококковой пневмонии [16].…”
Section: Introductionunclassified
“…S. pneumoniae can also cause invasive pneumococcal disease (IPD), including pneumonia, meningitis, osteomyelitis, and sepsis [ 2 ]. IPD is defined as a disease in which S. pneumoniae is cultured from normal sterile sites, such as blood, cerebrospinal fluid, pleural effusion, biopsy, joint effusion, or peritoneal effusion [ 3 ]. Previous reports found that pneumococcal conjugate vaccine (PCV) immunization could effectively prevent IPD [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%